2007
DOI: 10.1021/jf062497n
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Glycinin and β-Conglycinin Subunits that Contribute to the Increased Protein Content of High-Protein Soybean Lines

Abstract: Seed protein concentration of commercial soybean cultivars calculated on a dry weight basis ranges from approximately 37 to 42% depending on genotype and location. A concerted research effort is ongoing to further increase protein concentration. Several soybean plant introductions (PI) are known to contain greater than 50% protein. These PIs are exploited by breeders to incorporate the high-protein trait into commercial North American cultivars. Currently, limited information is available on the biochemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
12

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 42 publications
2
40
0
12
Order By: Relevance
“…Earlier studies showed that high-protein cultivars accumulated higher amounts of glycinin and β-conglycinin (Yaklich, 2001;Krishnan et al, 2007). This study confirmed this observation, except for genotypes KO5427, Table 3.…”
Section: Resultssupporting
confidence: 88%
“…Earlier studies showed that high-protein cultivars accumulated higher amounts of glycinin and β-conglycinin (Yaklich, 2001;Krishnan et al, 2007). This study confirmed this observation, except for genotypes KO5427, Table 3.…”
Section: Resultssupporting
confidence: 88%
“…So in other way of saying, soybean fiber (SPF) is natural plant-based man-made regenerated protein fiber that is produced from a blend of soybean protein and polyvinyl alcohol [9,18]. The soybean plant, its seeds and soybean protein fiber are shown in Soybeans contain great quantity of proteins, approximately 37-42%, compared to peanut (25%), milk (3.2%) and corn (10%) proteins [1,21]. Soybean proteins can be used as food, feed, textile fiber, pharmaceutical, ink, adhesive, emulsion, cleansing material and plastic [1,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, in other studies, soybean was successfully used to identify proteins involved in the response to pathogen invasion (Mithofer et al, 2002), salt stress (Aghaei et al, 2009), flooding (Shi et al, 2008), seed germination (Xu et al, 2006b), seed development (Hajduch et al, 2005), and UV radiation . Soybean peroxisomal proteins, xylem sap, and glycinins have also been characterized by proteomics (Natarajan et al, 2006Djordjevic et al, 2007;Krishnan et al, 2007;Arai et al, 2008). A protein reference map was also developed for soybean leaves, identifying 119 proteins (Xu et al, 2006a).…”
mentioning
confidence: 99%